Revision and extension of the group contribution equation of state to new solvent groups and higher molecular weight alkanes - Espinosa, Susana Noemi (2000)
The group contribution equation of state GC-EOS model is revised and extended. Pure group and binary interaction parameters are reported for the following new groups: ether CH2O, ester CH2COO/CH3COO, chloro-aromatic ACCl and triglyceride (TG) (CH2COO)2CHCOO.Interaction parameters between these groups and paraffin, olefin and CO2 groups were estimated using experimental vapor-liquid equilibrium data on binary mixtures. The original aromatic-paraffinic, CO2-paraffinic and CO2-aromatic interaction parameters, have been revised in order to improve phase equilibrium predictions in aromatic and high molecular weight organic compounds.